Conflicts of Criminal Jurisdiction in the European Union - Zimmermann, Frank (Bergen Journal of Criminal Law & Criminal Justice, 2015)
Conflicts of criminal jurisdiction between the Member States belong to the most difficult challenges that the European Union has to face in order to establish a true “area of freedom, security and justice”. This article starts with an analysis of the interests that are affected by such conflicts: on the one hand, they are most problematic for the individual because they can lead to repeated or simultaneous proceedings in different Member States and forum shopping by prosecution authorities. What is more, they can even make it impossible to foresee whether and how severely an act will be punished. Thus, essential criminal law and procedure guarantees like ne bis in idem, the principle of legality, the right to a court established by law as well as the right to an effective defence are jeopardised. On the other, the Member States involved often have a legitimate interest in prosecution—or non-prosecution—and risk to spend their financial and personnel resources for ineffective parallel proceedings. In order to avoid conflicts of criminal jurisdiction, various models are conceivable. However, the most convincing one—according to the author’s opinion—builds upon a combination of different elements: a hierarchy of jurisdictional links should form the basis, but it would have to be complemented with provisions allowing for more flexibility in precisely defined circumstances. With this in mind, this article calls for the adoption of an EU regulation in order to solve the most urgent problems arising from conflicts of criminal jurisdiction and makes concrete suggestions as to its drafting.